Seasonal variability of the Caspian Sea three-dimensional circulation, sea level and air-sea interaction - R. A. Ibrayev; E. Özsoy; C. Schrum; H. İ. Sur (Ocean Science, 2010)
A three-dimensional primitive equation model including sea ice thermodynamics and air-sea interaction is used to study seasonal circulation and water mass variability in the Caspian Sea under the influence of realistic mass, momentum and heat fluxes. River discharges, precipitation, radiation and wind stress are seasonally specified in the model, based on available data sets. The evaporation rate, sensible and latent heat fluxes at the sea surface are computed interactively through an atmospheric boundary layer sub-model, using the ECMWF-ERA15 re-analysis atmospheric data and model generated sea surface temperature. The model successfully simulates sea-level changes and baroclinic circulation/mixing features with forcing specified for a selected year. The results suggest that the seasonal cycle of wind stress is crucial in producing basin circulation. Seasonal cycle of sea surface currents presents three types: cyclonic gyres in December–January; Eckman south-, south-westward drift in February–July embedded by western and eastern southward coastal currents and transition type in August–November. Western and eastern northward sub-surface coastal currents being a result of coastal local dynamics at the same time play an important role in meridional redistribution of water masses. An important part of the work is the simulation of sea surface topography, yielding verifiable results in terms of sea level. The model successfully reproduces sea level variability for four coastal points, where the observed data are available. Analyses of heat and water budgets confirm climatologic estimates of heat and moisture fluxes at the sea surface. Experiments performed with variations in external forcing suggest a sensitive response of the circulation and the water budget to atmospheric and river forcing.